Pengaruh Dukungan Organisasi, Pengembangan Karir, Kepuasan Kerja, Budaya Organisasi, dan Work Life Balance terhadap Retensi Karyawan Produksi pada PT. Lucky Textile Semarang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Employee retention is a crucial aspect in maintaining smooth operations and the quality of human resources within an organization. This study aims to analyze the influence of organizational support, career development, job satisfaction, organizational culture, and work-life balance on production employee retention at PT. Lucky Textile Semarang. The study employed a quantitative approach with a survey method, distributing questionnaires to 307 respondents, selected using the Slovin formula, from a population of 1,325 production employees. Data analysis was performed using multiple linear regression using IBM SPSS Statistics 27. The results indicate that organizational support has no effect on employee retention, career development has a positive and significant effect on employee retention, job satisfaction has a positive and significant effect on employee retention, organizational culture has a positive and significant effect on employee retention, and work-life balance has a positive and significant effect on employee retention. These findings confirm that internal factors related to personal development, job satisfaction, and a healthy work culture are the most important factors in employee retention decisions. Therefore, companies need to prioritize career advancement strategies, improve working conditions, and strengthen organizational culture to maintain a competent workforce in the long term.